INFLUENCE OF THE MAINTENANCE ORGANIZATION ON THE TRACTION ROLLING STOCK OPERATION EFFICIENCY (Transport systems and technologies, 2018)
During the existence of railways, schedule preventive maintenance system of different levels has been established (M-i, where i – maintenance number, current repair (CR-j, where j – repair number and overhaul (O-m, where m – overhaul number).Frequency and amount of maintenance, CR are regulated by manufacturers and in the process of operation are partially adjusted according to the data from equipment failures. At the same time, the time between failures under different failure distribution laws has a large variance, which can lead to spreading of the timing of M, CR for a specific traction rolling stock (TRS).Under these conditions, against the background of the general deterioration of the technical state of TRS equipment, it is advisable to change to a mixed maintenance system, CR, which provides the organization of continuous monitoring of changes in the status of TRS equipment and the implementation of a TRC equipment maintenance system according to this condition.This article deals with the issues of the impact of maintenance organization under various laws of failures development on the traction rolling stock operation efficiency. Based on the choice of reliability parameters for various failure distribution laws of equipment, the values of reliability parameters are determined and the influence of the type of failure distribution law on the reliability parameters is analysed, for the evaluation of the effectiveness of the TRS equipment maintenance organization. The ratios obtained at the same time make it possible to determine not only the reliability indicators of the system, but also to calculate the optimal frequency and timing of maintenance in order to maintain the reliability of the system.
Keywords: traction rolling stock (TRS), failure distribution laws, TRS reliability indicators